Differentiated Learning through the Discovery Model and Gallery Walk to Accommodate Students' Learning Needs: A Needs Analysis - Himawan, Nur Arviyanto; Setyawan, Fariz; Istiandaru, Afit; Kardono, Kardono (Universitas Negeri Padang, 2024)
Meeting students' needs based on their characteristics is crucial to ensure they can learn comfortably and optimally. The objective of this research is to formulate learning plans that align with students' characteristics. This study adopts a descriptive qualitative approach, encompassing case studies and literature reviews. The research was conducted at Public Senior High School of Godean 1, with the subjects being 36 students from the 11th Science 3 class. Observation sheets and questionnaires were employed as instruments to identify students' characteristics, guided by the theory of differentiated learning. The analysis techniques involved data reduction, data presentation, and drawing conclusions/verification. Observation results indicate that the learning process has not effectively addressed students' Zone of Proximal Development (ZPD) and learning modalities. The majority of students operate at the potential level, with visual, kinesthetic, and audio modalities being the dominant ones in that order. A literature review on learning design suggests that differentiated learning, particularly through methods such as discovery learning and gallery walks, can serve as alternatives to meet these diverse learning needs.